Best alley shrubs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Researchers at the IITA (the International Institute of Tropical Agriculture) Rwanda Farming Systems Research Project have conducted a three-year trial of five alley-shrubs to discover which of these (Calliandra calothyrsus, Cassia spectabilis,...